Interaction potentials, spectroscopy and transport properties of C+(2PJ) and C+(4PJ) with helium - Tuttle, William D.; Thorington, Rebecca L.; Viehland, Larry A.; Wright, Timothy G. (Taylor & Francis, 2015)
We calculate accurate interatomic potentials for the interaction of a singly-charged carbon cation with a helium atom. We employ the RCCSD(T) method, and basis sets of quadruple-zeta and quintuple-zeta quality; each point is counterpoise corrected and extrapolated to the basis set limit. We consider the two lowest C+(2P) and C+(4P) electronic states of the carbon cation, and calculate the interatomic potentials for the terms that arise from these: 2-PI and 2-SIG+, and 4-PI and 4-SIG- , respectively. We additionally calculate the interatomic potentials for the respective spin-orbit levels, and examine the effect on the spectroscopic parameters. Finally, we employ each set of potentials to calculate transport coefficients, and compare these to available data. Critical comments are made in the cases where there are discrepancies between the calculated values and measured data.